The Tara compendium: feminine principles discovered - Adeu, Rinpoche (Rangjung Yeshe Publications, 2015)
Tara is an emanation of the mother of all the Buddhas of the three times. One important quality of Tara is her compassionate resolve to benefit all beings by removing whatever causes them to feel anxious or afraid. This book gives the devotee the tools to apply the energy and vitality of Tara in practice. Offering an overview of the many practices associated with this Buddha, it will enlighten the reader and affords the possibility to benefit others